Meta-analysis: menilai peningkatan keterampilan komunikasi melalui pendekatan pembelajaran discovery, problem-based, dan project-based - Wulan Nuzulia Putri; Ardi Ardi (IICET (Indonesian Institute for Counseling, Education and Therapy), 2023)
This research is based on several articles published in articles found on Google Scholar throughout Indonesia from 2016 to 2023. Variables were analyzed using the descriptive method of systematic literature review by collecting data from written sources such as books, journals and sources related to improving communication skills using discovery, problem-based, and project-based learning models. The research objective of this literature study is to see whether there is an increase in students' communication skills regarding discovery, problem-based and project-based learning models. The results of the literature study show that discovery, problem-based and project-based learning models are able to improve students' communication skills.